A Lumped-Element Decoupling and Matching Network for a Four-Element Mobile Handset MIMO Antenna - Riku Kormilainen; Rasmus Luomaniemi; Anu Lehtovuori; Ville Viikari (International Journal of Antennas and Propagation)
This paper presents the first realization of a lumped-element decoupling and matching network (DMN) for more than two-element mobile MIMO arrays. The realization of the DMN is based on an existing method, which is improved in terms of bandwidth and the number of network elements. The array is designed to operate in the 2.6–2.7 GHz LTE band. The DMN is applied to a four-element MIMO antenna array located on one side of the mobile phone chassis. The array initially has a strong coupling of −3 dB, which is improved to −7 dB with the DMN. In other words, this denotes a reduction of 30 percentage points in coupled power. The DMN also improves the total efficiency by 21 percentage points at best.